PERSOALAN DAN PROSES SOSIALISASI PENGELOLAAN SAMPAH BERBASIS PENGAJIAN DI DESA TEBING SARI MULYA KECAMATAN BELITANG MADANG RAYA KABUPATEN OKU TIMUR - Nugroho Nugroho; Zaki Faddad Syarif Zain (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2021)
Lack of knowledge and concern about environmental hygiene is the basis for the waste problem in Tebing Sari Mulya village. To implement waste management, public awareness is needed to change their behavior, from open dumping to sorting waste. Therefore, the community needs to be given socialization regarding knowledge about sorting the types of waste classified based on the types of waste. This paper will talk about the waste problem in Tebing Sari Mulya village, the socialization process and discuss the SWOT analysis regarding the possibility of forming a waste bank in this village. The conclusion of this activity is that it is possible to create a waste bank in Tebing Sari Mulya village, Belitang Madang Raya District, East OKU. In addition, the waste bank program can also be an instrument in forming a sakinah family